PENGARUH KARAKTERISTIK PETANI TERHADAP PENDAPATAN USAHATANI PADI DI DESA WONOKASIAN KECAMATAN WONOAYU KABUPATEN SIDOARJO TAHUN 2024 (The Influence of Farmers Characteristics on Rice Farming Income in Wonokasian Village, Wonoayu District, Sidoarjo Regency in 2024) - Patiung, Markus patiung; Inti, Ristani Widya; Rozci, Fatchur (Study Program of Agribusiness, Faculty of Agriculture, University of Wijaya Kusuma Surabay, 2024)
Farmer characteristics are important in determining changes in farming. Farmers who have good characteristics in developing their farming business can easily adjust to problems and use every opportunity to increase income. Farmers' income from rice farming is largely influenced by farmer characteristics. Farmer characteristics in this research are defined as a condition that is an attribute and inherent in a farmer's personality. The characteristics of farmers in Indonesia are correlated with the farmer's profile and the profile of their farming business. Farmer characteristics such as age, education, farming scale, number of family dependents, farming experience. The aim of this research is to analyze whether farmer characteristics influence rice farming income. This research is descriptive qualitative research. The method used is a purposive method in determining the location, a random method in determining respondents, an interview method in collecting data, and a data analysis method using regression analysis.Keywords: Analysis, Influence, Characteristics, Income